Cover Feature: Influence of Alkoxy Chain Length on the Properties of Two‐Dimensionally Expanded Azulene‐Core‐Based Hole‐Transporting Materials for Efficient Perovskite Solar Cells (Chem. Eur. J. 27/2019). Issue 27 (5th April 2019) - Truong, Minh Anh; Lee, Jaehyun; Nakamura, Tomoya; Seo, Ji‐Youn; Jung, Mina; Ozaki, Masashi; Shimazaki, Ai; Shioya, Nobutaka; Hasegawa, Takeshi; Murata, Yasujiro; Zakeeruddin, Shaik Mohammed; Grätzel, Michael; et al.
Abstract : A research‐grade perovskite solar cell in a natural environment is depicted on the cover art. The device is converting the bright sunlight to clean electricity, suggested by the healthy green vegetation in the surroundings. Also represented are tokens of the authors′ country and town, Mt. Fuji and Byodoin Temple. In the sky are the cloudlike azulene‐core based hole transport molecules reported in the paper. Multiple conformations of these molecules, responsible for their key material properties, are depicted. The facile interconversion between conformations, as demonstrated by theoretical calculations, can be imagined as clouds in the wind. More information can be found in the Full Paper by A. Wakamiya et al. on page 6741 .